"Arranging Life": The Immunitarian Building and its Openness to the world - Hilt, Annette (Itinerari, 2024)
If community, within which we give our live an institution, is the backdrop of both leading and understanding our living, how can we then possibly come to an understanding of belonging to something we share and have in common? This article tackles this question along R. Esposito’s paradigm of ‘immunity’, conceptions of empathy and E. Fink’s phenomenology of co-existence, arguing for a concept to make a sense of community within a narrative framework.